Evaluasi Degradasi Lahan Berdasarkan Identifikasi Perilaku Sungai dengan Pendekatan Geospasial di Sub Daerah Aliran Sungai Way Kandis - Didik Kuswadi (Jurnal Ilmiah Teknik Pertanian - TekTan, 2015)
Population growth, utilization of natural resources and the increasingly development will be influence on environmental changes such as environmental degradation, and resource. Land use patterns in a watershed was not accordanced with the rules of spatial planning can cause a variety of problems such as the formation of critical land and pollution. Based on administrative areas, Way Kandis subwatershed covered sub district Kemiling, Rajabasa, Tanjung Senang, Natar and Jati Agung. The objectives of this research were (1) to analyze of landuse changes in Way Kandis subwatershed, and (2) to analysed the impact of landuse changes on the water quality changes at Way Kandis River. Steps of this research were: (i) gathered information and data, (ii) analysed of land use Way Kandis subwatershed, (iii) observated of physical and chemical water quality Way Kandis River (iv) analysed of the impact landuse on water quality changes Way Kandis River. Based on the research, it can be some results: (i) Way Kandis Sub-Watershed covered an area of 17,320 ha; (ii) Landuse of Way Kandis Sub Watershed covered an area of 2,325 ha of plantations (13,42%), dryland farming an area of 11,227 ha (64,82%), settlements an area of 1,524 ha (8,80%), savanna an area of 536 ha (3,09%), open land an area of 1,130 ha (6,52%), shrubs an area of 31 ha (0,18%) and unidentified land an area of 547 ha (3,16%); (iii) The average of the DO value was 1.34-2.00 ppm. It indicated that the water of Way Kandis river included the category of Class IV with the provisions of the agricultural sector; (iv) The average of the COD value was 48-128 ppm. It showed that the water of the Way Kandis river included in the category of Class IV with the provisions of the agricultural sector; (v) The average TSS value was 123-421 ppm. It showed that the water of the Way Kandis river included in the category of Class III and IV with the provisions of the fisheries and agriculture, except the average TSS value in Rajabasa Village. Keywords: evaluation of the land degradation, river behavior, geospatial